NONHUMAN PRIMATE MODELS OF SOCIAL BEHAVIOR AND COCAINE ABUSE - Nader, Michael A. (2012)
RATIONALE: Although cocaine is often abused in social situations, very few animal studies examine the effects of cocaine in the context of social behavior. OBJECTIVES: This review highlights studies investigating the behavioral effects of cocaine in the context of social housing conditions using nonhuman primates. In addition, this review presents recent findings examining the effects of self-administering cocaine on social behavior and the effects of manipulations hypothesized to be stressful or enriching on the interactions between cocaine reinforcement and social rank. The following dependent variables are examined: 1) cocaine-induced changes in social behavior and 2) cocaine self-administration in cynomolgus monkeys of varying social ranks. The independent variables examined include several environmental and pharmacological manipulations. CONCLUSIONS: The studies reviewed here indicate that several variables can differentially affect cocaine self-administration when studied in a social context, rather than in individually housed animals. These variables include the social rank and sex of the individual, drug history, the nature of the “fear”-inducing manipulation, and the reliability of cortisol as an appropriate measure of “stress.” While the inclusion of socially housed animals necessitates larger sample sizes, animal models incorporating social behavior are more homologous to the human condition and should be implemented when possible.